2020
DOI: 10.1177/0265407520921460
|View full text |Cite
|
Sign up to set email alerts
|

Holding on and letting go: Memory, nostalgia, and effects of virtual possession management practices on post-breakup adjustment

Abstract: When people end their relationships, they must choose which parts of the relationship to remember and forget as they prepare themselves for future partners. This memory process is complicated by the recordability and permanence of mediated messages because individuals must actively curate their virtual possessions—such as pictures with a previous partner or online relationship statuses. Using the relational dissolution model framework, this study investigated the behaviors people use online to manage the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…Our sample also demonstrated some bias as over twice as many participants reported initiating the breakup as being the recipient (although this is consistent with other studies on SNSs and dissolution such as Brody et al, 2020). Future research efforts may wish to target those on the receiving end of a breakup.…”
Section: Discussionsupporting
confidence: 90%
“…Our sample also demonstrated some bias as over twice as many participants reported initiating the breakup as being the recipient (although this is consistent with other studies on SNSs and dissolution such as Brody et al, 2020). Future research efforts may wish to target those on the receiving end of a breakup.…”
Section: Discussionsupporting
confidence: 90%
“…However, victims of both ghosting and, to a greater extent, orbiting reported some actions on social networking sites (e.g., increasing privacy settings, blocking the former partner and friends, deleting chat messages) that can be ascribed to the grave-dressing process. These behaviors deserve further attention, as also recent research highlighted the impact of keeping and deleting virtual possessions (e.g., pictures, messages, and relationship status on social networking sites) on post-breakup adjustment (Brody et al, 2020).…”
Section: Links With Relationship Dissolution Literaturementioning
confidence: 99%
“…For the participants in this study, the average time since the breakup was approximately 1.5 years with a maximum of 5 years. Other research in the literature has also had average times since the breakup greater than a year and up to 7 years (Hawley et al, 2015; Marshall et al, 2013; Shulman et al, 2017) In this regard, recent research has indicated that virtual possessions and social networks sites can make it harder to recover from a romantic breakup as a result of revisiting memories from the broken relationship and maintaining contact or surveillance of the ex-partner (Brody et al, 2020; Spottswood & Carpenter, 2020). This can extend the feelings and thoughts about the broken relationship, including the breakup distress, for periods of time longer than prior to the digital age and the advent of the social network online sites.…”
Section: Discussionmentioning
confidence: 99%